#TITLE_ALTERNATIVE# - BUDIRAHARJO (NIM: 25313022), AGUNG
Organic-Pb or organolead compound is a derivative of Pb metal which have toxicity levels four times higher than the pure metal Pb and Pb ionic. In this research, the modification of tannin from the Strobilanthes crispus leaves biomass was utilized as an adsorbent material for the removal of organolead from artificially contaminated solution. Biosorbent used in this study consists of three types: biosorbent from biomass without treatment (BTP), biosorbent treatment polymerization from the biomass (BDP), and biosorbent treatment polymerization from the tannin extract from biomass (BEP). Scanning Electron Microscopy (SEM), moisture content, ash content, volatile content, and fixed carbon content was conducted to determine the physical and chemical characteristics of biosorbent. Batch experiments were used to predict the adsorption capacity of lead ion. Different parameters affecting the adsorption process were tested including initial adsorbent particle size, adsorbent dose, contact time and adsorbate dose. The adsorption process of organolead was tested with Langmuir and Freundlich model. The optimum conditions on the use BTP include the use of a dose of 50g/L, the pore size of 100 mesh, for 10 minutes contact time with the allowance organolead happens reached 99%. The optimum conditions on the use of BEP include the use of a dose of 50g/L, the pore size of 100 mesh, 60-minute contact time with the allowance organolead happens reached 88.4%. The optimum conditions on the use of BDP include the use of a dose of 10g/L, the pore size of 100 mesh, for 80 minutes of contact time with the allowance organolead happens reached 99.12%. Isotherms were formed closer to the model Freundlich for BTP and BDP, while BEP approached Langmuir models. For industrial applications biosorben types of BTP is considered the most economically viable.